Liminal Warfare in the Israel-Palestinians War Case Study: Post-October 7, 2023 Attacks - M, Faiq Dhiya Ulhaq; Priyanto, Priyanto; Afifuddin, M. (PT FORMOSA CENDEKIA GLOBAL, 2025)
The Israel-Palestinians conflict has experienced a new escalation after the October 7, 2023 attacks, which reflects the dynamics of liminal war—a war strategy that falls between conventional and unconventional. This study analyzes how liminal warfare takes place in such conflicts, including its actors, strategies, and impacts on regional and international stability. With a qualitative case study method, this study examines official reports, expert analysis, and data from international organizations. The results show that this war is characterized by guerrilla tactics, precision strikes, as well as information warfare that affects global perception. These findings enrich our understanding of modern warfare and security strategies in conflict zones.